PEDAGOGICAL PRINCIPLES OF USING GAME TECHNOLOGIES IN ENGLISH TEACHING (World Bulletin of Social Sciences, 2022)
This article describes the popularity of the English language today and the methods of using game technologies in teaching English to children of preschool and primary school age, studying children's interests and improving the effectiveness of the lesson, as well as appropriate evaluation of children's actions
Keywords: method; game; technology; innovation